Female Superiority of Stereotypical Barbie in Greta Gerwig’s Barbie Movie Script - Dewi Ayu Rengganis; Rommel Utungga Pasopati (Gudang Jurnal Multidisiplin Ilmu, 2024)
This study aims to understanding the concept of female superiority in Barbie movie script written by Greta Gerwig. The movie was published in 2023. The movie reflects female superiority on the main character Stereotypical Barbie. The researchers use qualitative approach, focusing on the context and some subjective interpretations in detail. The analysis reveals that Stereotypical Barbie as the main character being superiority to around her and belong to Ken as the male character. The superiority is going on among womanness of the Stereotypical Barbie that is reflected in herself as an Alpha Female. In conclusion, female superiority in Barbie movie is such proof that women could be anything beyond any dictation from male beings.